Participation in Collision Sports and Cognitive Aging Among Swedish Twins. Issue 12 (18th June 2021) - Weiss, Jordan; Rabinowitz, Amanda R; Deshpande, Sameer K; Hasegawa, Raiden B; Small, Dylan S
Abstract: We examined the association between early-life participation in collision sports and later-life cognitive health over a 28-year period in a population-based sample drawn from the longitudinal Swedish Adoption/Twin Study of Aging (1987–2014). Cognitive measures included the Mini-Mental State Examination and performance across multiple cognitive domains (e.g., global cognition, verbal ability, spatial ability, memory, processing speed). Among a sample of 660 adults (mean age at baseline, 62.8 years (range: 50–88); 58.2% female), who contributed 10, 944 person-years of follow-up, there were 450 cases of cognitive impairment (crude rate = 41.1/1, 000 person-years). Early-life participation in collision sports was not significantly associated with cognitive impairment at baseline or with its onset over a 28-year period in a time-to-event analysis, which accounted for the semi-competing risk of death. Furthermore, growth curve models revealed no association between early-life participation in collision sports and the level of or change in trajectories of cognition across multiple domains overall or in sex-stratified models. We discuss the long-term implications of adolescent participation in collision sports on cognitive health.